Self-expanding and balloon-expandable transfemoral transcatheter aortic valve replacement: in-hospital outcomes in Germany. (14th October 2021) - Oettinger, V; Zehender, M; Bode, C; Kaier, K; Von Zur Muehlen, C; Stachon, P
Abstract: Background: The impact of valve type used in transfemoral transcatheter aortic valve replacement (TF-TAVR) on outcomes is currently under discussion. Purpose: We examine the in-hospital outcomes of balloon-expandable (BE) and self-expanding (SE) valves in a complete national cohort in Germany in 2018. Methods: All 17, 295 patients receiving TF-TAVR with BE (N=9, 882) or SE (N=7, 413) valves in Germany in 2018 were identified. Outcomes were analyzed for the endpoints in-hospital mortality, major bleeding, stroke, acute kidney injury, postoperative delirium, mechanical ventilation >48h, length of hospital stay, and reimbursement. Since there was no randomization of patients to the two treatment options, logistic or linear regression models were carried out using 22 baseline patient characteristics and center-specific variables as potential confounders. Propensity score methods served as sensitivity analysis. Results: Both valve types differed significantly in baseline characteristics with higher EuroSCORE (p<0.001), age (p<0.001) and rate of female sex (p<0.001) in patients treated with SE valves. After risk adjustment, there were no marked differences in outcomes for in-hospital mortality (risk adjusted odds ratio (aOR) for SE instead of BE: 0.94 [95% CI 0.76; 1.17], p=0.617), major bleeding (aOR 0.91 [0.73; 1.14], p=0.400), stroke (aOR 1.13 [0.88; 1.46], p=0.347), acute kidney injury (aOR 0.97 [0.85; 1.10], p=0.621), postoperative delirium (aOR 1.09 [0.96; 1.24], p=0.184), mechanical ventilation >48h (aOR 0.98 [0.77; 1.25], p=0.893), length of hospital stay (risk adjusted difference in days of hospitalization: −0.05 [−0.34; 0.25], p=0.762) and reimbursement (−€72 [−€291; €147], p=0.519). Similar results were found using propensity score methods. Conclusion: Outcomes in contemporary TF-TAVR procedures are broadly equivalent regardless of the valve type used. Major complications rarely occur in both types of valve. Funding Acknowledgement: Type of funding sources: None.